INTERVAL DATA ENVELOPMENT ANALYSIS AND AN APPLICATION IN TURKISH BANKING SECTOR - Budak, Huseyin; Erpolat, Semra (European Scientific Journal, ESJ, 2013)
Interval Data Envelopment Analysis (Interval DEA) which is the approach that could make efficiency measurement with interval or fuzzy input and output data of Data Envelopment Analysis (DEA) which is used to measure the relative efficiencies of Decision-Making Units (DMU) in multi-input and multi-output processes was examined in this study. This model which was based on arithmetic operations with interval numbers, provides, unlike other DEA models, the relative efficiency measurements of DMU with inputs and outputs which had interval data, by using fixed and combined production limit without the need of extra variable or scale transformation. Interval efficiency of 21 commercial banks in Turkish banking sector in 2011 was calculated to show how related method was implemented in this study.